Alteration of muscle fibre composition in male junior elite road cyclists over the competition period - Frse, S.; Looser, P.; Gehlert, S.; Boelck, B.; Bloch, W. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The cellular specialization of skeletal muscle fibres enables remodeling of the muscle`s structural makeup according to alterations in functional demand. The capability to load-dependent muscle fiber type specific adaptations demonstrates the enormous plasticity of human skeletal muscle and the specificity of the adaptive response. Close to the annual road cycling exercise planning we focused on the competition period to investigate the chronic skeletal muscle response to endurance exercise after the repeated impact of stimuli that occurs with competition and training performance. The aim of this study was to investigate the activity-dependent muscle plasticity allowing for phenotypic stimuli and consequent muscular modifications. Ten male elite cyclists (18.1±0.57yr) participated in this study. They had a history of >5yr of race experience and were part of competitive cycling teams at national level. In february (Pre) before beginning of the competition period and at the end in october (Post) the subject`s performances have been tested by an incremental cycling step test to exhaustion. There was a spirometry and lactate survey. After the following two days each with a moderate cycling endurance exercise (~60-65% of subject`s V˙o2peak;~90-120min) standardized muscle biopsies were taken of vastus lateralis muscle by needle biopsy the third day. The analysis of fibre composition was effected by histochemical ATPase-staining. The muscular monitoring over the competition period illustrates no difference in mean value of the absolute ratio of fast twitch (Pre:36.29±2.56%;Post:41.14±9.99%) and slow twitch fibres (Pre:63.71±2.56%;Post:58.86±9.99%). But remarkable is the individual big range of relative remodelling of fibre types IIA and IIX within the fast twitch fibre spectrum. Estimable is the fibre pattern of two subjects with a reduction of fatigue-resistance phenotype decreased by 31% and an accession of fibre type II increased by 59% compared with Pre (p<0.05). However the analysis of fibre composition shows muscular modifications of the fast twitch fibre distribution-the rate of slow twitch fibres remains nearly constant. In conclusion, the profile of muscle perturbation exerts essential control over the muscle phenotype. After execution of the extensive endurance winter training the subjects have a divergent fibre spectrum from the competition period. The chronic response to high intensity sessions over the competition period shows the cellular specialization that allows the recruited muscle fibres to adjust its metabolic and contractile makeup in response to alterations in functional demands. Thus we have to think about the extensive winter exercise regime and an improvement of exercise regulation that pass into the competition period.